(Invited) Plasma Assisted Oblique Angle Deposition of Transparent and Conductive in-Plane Anisotropic ITO Thin Films. (21st April 2017) - Parra-Barranco, Julian; Sanchez-Valencia, Juan Ramon; Aparicio, Francisco J.; Garcia-Garcia, Francisco; Ferrer, Francisco J.; Rico, Victor; Lopez-Santos, Carmen; Borras, Ana; Gonzalez-Elipe, Agustin R.; Barranco, Angel
Abstract : Oblique angle deposition (OAD) is a powerful technique for the fabrication of porous nanostructured oxide thin films. OAD films typically present a columnar tilted nanostructure due to geometrical shadowing effects during the thin film growth. In this work, we study the fabrication of transparent and conducting indium tin oxide films (ITO) by OAD assisted by a microwave ECR plasma. The objective of assisting the deposition with a plasma discharge is to modify the growth mechanism of the OAD process introducing additional parameters to control the columnar microstructure, composition, porosity of the films. The results indicate the OAD ITO deposition assisted by the plasma discharge is a very effective process to develop in-plane structural anisotropy in the ITO nanocolumnar films what determines their electrical properties.